2006
DOI: 10.1063/1.2206701
|View full text |Cite
|
Sign up to set email alerts
|

Observation and analysis of percolation behavior in carbon microcoils/silicone-rubber composite sheets

Abstract: The electrical properties of carbon microcoils ͑CMCs͒/ silicone-rubber composites were studied on the changes in the values of the electrical parameters ͑impedance, phase angle, resistance, and capacitance͒ as a function of the CMC content in the matrix, using an impedance analyzer in the frequency range from 40 to 200 kHz. Percolation paths were observed at a 3 wt % CMC content in the matrix. The properties of the composites were separated at the percolation threshold. The capacitance with a small value was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Processing variables (i.e., the type of filler, volume fraction of filler in the composite) and operating variables (i.e., strain amplitude, strain rate, frequency, and temperature of testing) have a significant effect on the dynamic properties of the polymers. 2 Recently, much attention is being focused on the applicability of new generation fillers like carbon silica dual-phase filler (CSDPF), 3 carbon nanotubes, 4 conductive carbon black, 5 and nano graphite. 6 Although there have been many studies on the effect of addition of conductive carbon black in elastomer matrices, no literature has been reported in CSM vulcanizates.…”
Section: Introductionmentioning
confidence: 99%
“…Processing variables (i.e., the type of filler, volume fraction of filler in the composite) and operating variables (i.e., strain amplitude, strain rate, frequency, and temperature of testing) have a significant effect on the dynamic properties of the polymers. 2 Recently, much attention is being focused on the applicability of new generation fillers like carbon silica dual-phase filler (CSDPF), 3 carbon nanotubes, 4 conductive carbon black, 5 and nano graphite. 6 Although there have been many studies on the effect of addition of conductive carbon black in elastomer matrices, no literature has been reported in CSM vulcanizates.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the arraying of the CMC in the silicone rubber matrix resulted in a significant increase in the tactile sensitivity. [3][4][5] However, it is difficult to disperse CMC in various solvents and polymer matrices uniformly because of the unique morphology. We have pointed out that the grafting of polymers onto the surface is effective method for the destruction of aggregation of nanoparticles and entanglement of nanofibers.…”
mentioning
confidence: 99%
“…It was found that incorporation of carbon nanocoils in epoxy nanocomposites can enhance the mechanic properties of the epoxy nanocomposites [122][123][124][125]. Besides, the coiled CNT/silicone-rubber composites show high resistive sensitivity, relying on the densi-ty of the carbon nanocoil [126,127]. In addition, metal-coated carbon nanocoils can also display some properties different from the pristine coiled CNTs.…”
Section: Applicationsmentioning
confidence: 99%